2017
DOI: 10.1038/s41598-017-12427-y
|View full text |Cite
|
Sign up to set email alerts
|

Pristine populations of habitat-forming gorgonian species on the Antarctic continental shelf

Abstract: Declines in the abundance of long-lived and habitat-forming species on continental shelves have attracted particular attention given their importance to ecosystem structure and function of marine habitats. The study of undisturbed habitats defined as “pristine areas” is essential in creating a frame of reference for natural habitats free of human interference. Gorgonian species are one of the key structure-forming taxa in benthic communities on the Antarctic continental shelf. Current knowledge of the diversit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 90 publications
0
14
0
Order By: Relevance
“…While these methods are excellent for species identification of sessile and slow-moving benthic organisms, they are not as efficient at capturing more mobile species, are destructive, and cannot describe species behaviours and interactions present in the ecosystem. Advances in technology (e.g., photographic and video imagery, SCUBA, remotely operated vehicles, autonomous underwater vehicles) have increased the rate of new species discoveries for the WAP, as well as helping to develop a better understanding of ecosystem patterns and processes in the region [ 2 , 25 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…While these methods are excellent for species identification of sessile and slow-moving benthic organisms, they are not as efficient at capturing more mobile species, are destructive, and cannot describe species behaviours and interactions present in the ecosystem. Advances in technology (e.g., photographic and video imagery, SCUBA, remotely operated vehicles, autonomous underwater vehicles) have increased the rate of new species discoveries for the WAP, as well as helping to develop a better understanding of ecosystem patterns and processes in the region [ 2 , 25 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gorgonians are one of the most conspicuous organisms in tropical, temperate and polar marine animal forests 14–16 , and they are considered to be “eco-engineers” due to their ability to modify the surrounding habitat 17 . Except for mixotrophic species, gorgonians are passive suspension feeders that rely completely on ambient flow and particle abundances in the water masses for feeding 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, cold-water corals are recognized as an important component of deep-water ecosystems world-wide for their role as ecosystem engineers providing habitat for many other organisms (Rogers et al, , 2008Miller et al, 2012), and recognition of their vulnerability has put them on the international conservation agenda (Roberts and Cairns, 2014). Corals are diverse (Rogers et al, 2008;Ambroso et al, 2017), extremely slow growing (Roark et al, 2005;Rogers et al, , 2008Peck and Brockington, 2013;Martinez-Dios et al, 2016) and vulnerable to fishing gear (Rogers et al, 2008;Maynou and Cartes, 2012), and communities can be tens of 1,000s of years old. Recovery times of populations, therefore, are estimated to be in the 100s or 1,000s of years (Rogers et al, 2008) and that is especially true for the many brooding species (Ambroso et al, 2017) found in the Southern Ocean.…”
Section: Discussionmentioning
confidence: 99%